Laparoscopic versus open surgery in the treatment of colorectal cancer - Abd-Elshafy, Yasser Mohammad; Mohammad, Islam Mohammad; Ashry, Hazem Nour Abdelatif; Zaitoun, Mohammad Abdullah (International Surgery Journal, 2021)
Because of the initial case study results suggesting high recurrence rates at port sites, adoption of the laparoscopic approach for colorectal cancer treatment was slow. Surgical resection remains the cornerstone and most important facet in management of colon cancer. The use of minimally invasive approach in colorectal surgery has been reported by several authors in the literature. Some difficult about the use of laparoscopic surgery for colorectal cancer still raises, particularly with the technique’s complexity, learning curve and longer duration. Scientific literature published from January 2010 to April 2020 was reviewed. Phase III randomized clinical trials were included. Analysis of the scientific literatures confirmed that for the curative treatment of colon and rectal cancer, laparoscopy is not inferior to open surgery with respect to overall survival, disease-free survival and rate of recurrence. Laparoscopic resection can be considered an option for the curative treatment of colon and rectal cancer; but must take into consideration surgeon experience, tumour stage and potential contraindications; and that laparoscopic resection for rectal cancer be performed only by appropriately trained surgeons.